1978
DOI: 10.1007/bf00426967
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methylphenidate on repeated acquisition of Serial Discrimination Reversals

Abstract: Rats were trained to bar-press for sucrose solution in the presence of one of two stimulus conditions. On each daily training session, the stimulus during which bar-pressing was reinforced was reversed. The subjects were trained in this Serial Discrimination Reversal procedure until successive acquisitions of the discrimination had stabilized. Drug treatments consisting of saline or 0.25, 1.0, 2.0, 4.0, 6.0 or 8.0 mg/kg of methylphenidate were then administered 20 min prior to the daily training sessions. Acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Because the baseline levels accuracy and speed in the acquisition component were generally well below those in the performance component, it would appear that the failure to detect improved accuracy can not simply be attributed to a low ceiling. Those studies that have detected learning enhancement by stimulants generally have used either a spatial learning task (Zhu, et al, 2007) or a discrimination-reversal procedure (Calhoun and Jones, 1974; Handley and Calhoun, 1978), although it should be noted that Paule & McMillan (1984) found enhancement at low d-amphetamine with the incremental repeated acquisition task. None of these studies used a RAP procedure, but RAP adaptations of spatial navigation tasks and reversal learning tasks are available (Galizio et al, 2006; Keith and Galizio, 1997) and it would be interesting to examine the effects of MA and MPD using these procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the baseline levels accuracy and speed in the acquisition component were generally well below those in the performance component, it would appear that the failure to detect improved accuracy can not simply be attributed to a low ceiling. Those studies that have detected learning enhancement by stimulants generally have used either a spatial learning task (Zhu, et al, 2007) or a discrimination-reversal procedure (Calhoun and Jones, 1974; Handley and Calhoun, 1978), although it should be noted that Paule & McMillan (1984) found enhancement at low d-amphetamine with the incremental repeated acquisition task. None of these studies used a RAP procedure, but RAP adaptations of spatial navigation tasks and reversal learning tasks are available (Galizio et al, 2006; Keith and Galizio, 1997) and it would be interesting to examine the effects of MA and MPD using these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the effects of psychomotor stimulants on learning, but the results have been mixed. For example, some studies have found only disruption of learning by amphetamines or MPD (Braida et al, 2002; Chuhan and Taukulis, 2006; Mayorga et al, 2000; Nagai, et al, 2007), while others have found enhancement of learning at some doses of amphetamines or MPD (Calhoun and Jones, 1974; Handley and Calhoun, 1978; Zhu et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, drugs known to have deleterious effects on cognition, for example, the monoaminergic stimulant methamphetamine and the primary psychoactive ingredient in marijuana Δ 9 -tetrahydrocannabinol produce dose-dependent decrements in the acquisition rate of novel discriminations (Galizio et al 2009; Kangas and Bergman 2012; Nakamura-Palacios et al 2000; Winsauer et al 1999), whereas other drugs, for example, the attention enhancer methylphenidate, have been shown to increase the rate of discrimination reversals (Handley and Calhoun 1978). Overall, these assays provide a useful means to assess both the short-term and long-term adverse effects of abused drugs and the safety of novel therapeutics with regard to well-established learning processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed acute effects of psychomotor stimulants using various models of learning in nonhumans with somewhat mixed results. Although most studies have found only impairment of learning across dose-response functions for MDMA (e.g., Braida et al, 2002; Byrne et al, 2000), MA (e.g., Mayorga et al, 2000) and MPD (e.g., Chuhan & Taukulis, 2006; Mayorga et al, 2000), cognitive enhancements by these drugs have also been reported (e.g., Calhoun & Jones, 1974; Handley & Calhoun, 1978; Quinteros-Munoz et al, 2010; Tian et al, 2009; Zhu et al, 2007). …”
mentioning
confidence: 99%